Decreased cardiac output: an integrative review - Ricardo Costa da Silva; Micaelle Costa Gondim; Gabriela Moreira Melo; Viviane Martins da Silva; Agueda Maria Ruiz Zimmer Cavalcante; Miriam de Abreu Almeida; Amália de Fátima Lucena (Associação Brasileira de Enfermagem, 2023)
ABSTRACT Objective: to identify, in the scientific literature, the defining characteristics and contributing factors (related factors, associated conditions and populations at risk) for nursing diagnosis decreased cardiac output. Method: an integrative literature review, conducted between September and October 2020, with an update in March 2022, in the MEDLINE via PubMed, LILACS, SciELO, CINAHL and EMBASE databases. Using acronym PEO, studies published in the last 10 years in Portuguese, English and Spanish were included. A descriptive analysis was carried out to present the elements mapped in the literature. Results: analysis of 31 articles identified different elements, highlighting 4 new related factors: hyperglycemic stress, prone position, left lateral position, sleep deprivation. Individuals with a history of cardiovascular disease and males were identified as possible populations at risk. Final considerations: the elements for decreased cardiac output, identified in the literature, add evidence that justifies the permanence of this diagnosis in the NANDA-I classification.